Odontogenic Fibromyxoma of the Maxilla: A Case Report and Review of the Literature - Eva-Maria Dietrich; Styliani Papaemmanouil; Giorgos Koloutsos; Hlias Antoniades; Konstantinos Antoniades (Case Reports in Medicine)
Fibromyxoma represents a rare benign neoplasm that mostly affects the posterior region of the mandible. Here, we report the case of a 46-year-old male with a swelling of the right maxilla. After proper diagnosis, he was treated with enucleation and curettage of the tumor. The defect was filled with a pedicled buccal fat pad flap. The mesenchymal origin from the dental follicle of the fibromyxoma is the most plausible explanation. Radiological examination with MRI, CT, and conventional radiography contributes to the differential diagnosis from other benign tumors, such as the ameloblastoma. Its management is surgical and comprises enucleation and curettage or en bloc resection. Patients must be monitored for at least two years postoperatively in order to diagnose possible recurrence. According to the literature, the maxilla is a rare location of a fibromyxoma and, to our knowledge, our case is the 30th presented case of a fibromyxoma of the maxilla.